Knowledge of women who have sex with women about Sexually Transmitted Infections and AIDS - Parenti, Ana Beatriz Henrique [UNESP] (2023)
This article aims to study the knowledge of women who have sex with women about Sexually Transmitted Infections and AIDS. Cross-sectional study of 260 women, 81 women who either have sex with women or with men and women (WSW) and 179 women who have sex exclusively with men (WSM). Data were collected in 2019/2020 by means of a form and validated instruments. To study the association between sexual partnership and level of knowledge about Sexually Transmitted Infections and AIDS, multiple Cox regression models were adjusted, producing significant associations of p<0,05. The median percentage of correct answers was lower among WSW when compared to WSM [68% (1896) vs 75% (14-96); p=0.023]. Having sex with woman [PR=2.36 (1.07-5.21); p=0.033] and less than 11 years of schooling [PR=2.64 (1.12-6.21); p=0.026] were independently associated with low knowledge. WSW had a lower level of knowledge about Sexually Transmitted Infections and AIDS than WSM, and lower education was independently associated with this finding.